A study on Glycine max (l.) Merril (Soybean): Exploring the impact of mycoflora on the nutritional quality of Glycine max seeds (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The soybean (Glycine max (L.) Merril) is a commercially significant leguminous seed crop forfeed and food applications, containing 40 seed protein and 20 oil. Among the major oil crops, soybeanranks first in world production in international trade markets, followed by cottonseed, groundnut(peanut), sunflower seed, rapeseed, linseed, sesame seed, and safflower. Many oilseed crops' seeds areknown to have substantial mycoflora. The current study's aim was to determine fungus linked withdistinct varieties of soybean, as well as isolate and identify them. The presence of mycoflora in seedswas determined using several cultivars. For amino acids, lipids, and enzymes, qualitative estimate was acritical step. The effect of plant extracts on cereal seed mycroflora, seed germination, seedlingemergence, root and shoot lengths was investigated.The results show that Alternaria tenuis, Aspergillusdefects, Rhizopusstolonifer, and Curwlarialumtaare key fungus for altering nutritional value, and theirproliferation causes substantial quality of the seeds.As a consequence, it may be concluded that thesefungi have well-equipped enzyme systems to degrade and use any form of storage molecule found in oilseeds. However, the degree of enzyme production differed across the mycoflora, which might beattributed to variances in adaptation among different fungi.